Experimental Study on Axial Compression Behavior of Masonry Columns' Strengthening with Bamboo Scrimber Bar Mesh Mortar Layer. (15th February 2020) - Liu, Hongyao; Lei, Min; Chen, Bowang
Abstract : We propose a new method to strengthen structural masonry. To study on the axial compression behavior of masonry columns' strengthening with a bamboo scrimber bar mesh mortar layer, axial compression tests of twelve masonry columns have been completed: nine strengthened columns and three unstrengthened columns. The failure process, bearing capacity, and failure mode are carried out. The strengthening method of bamboo scrimber bar mesh mortar layer permits the upgrade of the columns' bearing capacity. The effects of bamboo bar ratio and mortar strengthening ratio on bearing capacity of the reinforced columns are compared. We propose the method for calculating the axial bearing capacity of such a reinforced column. The calculation results agree well with the experimental results, and the research results are available for engineering application.